Rancang Bangun Aplikasi Administrasi Pengelolaan Surat Masuk Dan Surat Keluar Pada Kantor Pelayanan Kekayaan Negara Dan Lelang Bandung - Putra, Septian Dwi Kusuma; Sulistiowati, Sulistiowati; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract:Â State Assets and Auction Service Office (KPKNL) Bandung is a vertical institution of the Directorate General of State Assets Management (DJKN) of the Ministry of Finance. The existing problems in KPKNL Bandung is uncontrolled mail management, such as errors in recording, archiving and distribution. It is occured due to the abbundant number of incoming and outgoing mail, as well as to support the Standard Operating Procedure (SOP) on archival regulated by the Director General of State Assets Management No. 145 / KN / 2013.The solution offered is in the form of computerized application for incoming and outgoing mail administrative management that can produce a computerized data and facilitate the execution of the groove mail administration in accordance with the stages of Software Development Life Cycle (SDLC) that includes the step of system planning, system analysis, system design, and implementation of the system.The results showed that the application has been made to help the recording, archiving, and monitoring the distribution of mails, layout archiving and sorting of mailings in accordance with the SOP. In addition, this application can also generate archiving reports that can be used as the basis for decision making by the officers of KPKNL Bandung.Keywords: Application, Mailing Administration, Standard Operating ProcedurÂ